STRATEGI PENGEMBANGAN STRATEGI MARKETING PADA UMKM KERIPIK PISANG DI DESA SEMENPINGGIR - Suhartono, Edy; Azhari; Ardyani, Ryzki Novica; Sakti, Tengku Muda Agam (Jurnal Abdi Masyarakat, 2025)
The Konco Dewe Banana Chips Small and Medium Enterprise (SME) in Bojonegoro Regency faces various challenges, particularly in product marketing and the use of digital technology. This mentoring program aims to help the SME understand and implement digital marketing strategies through e-commerce platforms to increase product visibility and sales. The mentoring program includes registering the SME on Facebook and Instagram marketplaces, optimizing business pages, and adding business locations to Google Maps. The methods used are hands-on training, technical guidance, and digital marketing simulations. The training includes uploading products to marketplaces with attractive descriptions and quality photos. The mentoring results show an increase in partners' understanding of digital technology, increased product visibility on e-commerce platforms, and successful registration of business locations on Google Maps, making it easier for customers to find production locations. This mentoring contributes to the development of science and technology, particularly in the adaptation of digital marketing by small-scale SMEs. Through this digital strategy, the Konco Dewe SME is expected to expand its market, increase its competitiveness, and strengthen its business position in both local and digital markets